Implementasi Pembelajaran Berdiferensiasi untuk Mengakomodir Kebutuhan Belajar Murid - Nafiah, Tri (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2024)
Every student has different learning needs. One learning approach that can accommodate differences in student learning needs is differentiation learning. The purpose of this research is to describe the implementation of differentiated learning to accommodate the learning needs of fifth grade students at SD Negeri Semarang 1, Yogyakarta. This research was carried out using qualitative research methods with the Miles and Hubberman case study approach. The stages in this study include data reduction, data presentation, and drawing conclusions. The results of the study show that differentiated learning is implemented through 3 stages, namely the planning, implementation and reflection stages. The differentiation strategy used is content, process and product differentiation. Differentiated learning can accommodate all student needs, increase learning motivation, and encourage the realization of student well being.